2023
DOI: 10.30935/cedtech/13013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficacy between game-based learning and pamphlet on enhancing recognition of common cutaneous malignancies in Thai younger adults

Abstract: Cutaneous malignancy is one of the leading causes of cancer-related morbidities and mortalities. Patient self-screening is helpful for early detection. Among educational pedagogies, game-based learning (GBL) has received increasing attention in recent years. We appraised the effectiveness of GBL, using Wordwall, to enhance cognitive performances pertaining to fundamental knowledge of cutaneous malignancies and perspectives on the intervention compared with a digital pamphlet. This multi-center study utilized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…34 The study by Nadia et al 35 also reported that using the Wordwall application in online mathematics learning led to improved student learning outcomes for 5 thgrade students at MI Muhamadiyah 1 Gresik during the COVID-19 pandemic. Another finding in the study by Mettarikanon et al 16 in Thailand revealed that the understanding level of participants in the intervention group, who utilized Wordwall Game, extended beyond a mere increase in general knowledge related to the material studied. Significantly, it also enhanced participants' capacities for recognition, comparison, distinction, and analysis through repetitive practice.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…34 The study by Nadia et al 35 also reported that using the Wordwall application in online mathematics learning led to improved student learning outcomes for 5 thgrade students at MI Muhamadiyah 1 Gresik during the COVID-19 pandemic. Another finding in the study by Mettarikanon et al 16 in Thailand revealed that the understanding level of participants in the intervention group, who utilized Wordwall Game, extended beyond a mere increase in general knowledge related to the material studied. Significantly, it also enhanced participants' capacities for recognition, comparison, distinction, and analysis through repetitive practice.…”
Section: Discussionmentioning
confidence: 87%
“…15 Game-based interventions promote motivation, enjoyment, and strong performance among learners. 16 ICT has modernized education during the COVID-19 pandemic by offering interactive digital media exercises. A popular educational software used for this purpose is Wordwall.…”
Section: Introductionmentioning
confidence: 99%